KORELASI PENGUASAAN KOSAKATA DENGAN KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII SMP NEGERI 17 PADANG - Plandra, Bustia; Thahar, Harris Effendi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT  There are three purpose of this research. The first,to describe  Vocabulary The second, to describe Fantasy Story Text Writing Skills. And the third, to describe the Correlation of Vocabulary Mastery with Fantasy Story Text Writing Skills. The kind of this research is quantitative descriptive method with correlational approach. The design used in this research is the correlational design. The sample in this research is determined by proportional random sampling of 20% of the population, namely 40 students. The instrument of this research is an objective test to measure vocabulary mastery and performance tests to measure fantasy story text writing skills. There are three results of this research. First, the writing skills of fantasy text of the VII Grade Students of SMP Negeri 17 Padang are in Very Well (BS). The second, Vocabulary Mastery of the VII Grade Students of SMP Negeri 17 Padang are in Very Well (BS). And the third, the vocabulary mastery has a correlation with the fantasy story writing skills of VII grade students of SMP Negeri 17 Padang with a degree of freedom n-2 at a 95% confidence level. Tcount value (5.23) is greater than Ttable (1.68). Therefore, H0 is rejected and H1 is accepted because the test results prove that Tcount is greater than Ttable. Based on the results of the research, it can be concluded that the mastery of vocabulary correlated with the writing skill of fantasy story text. Kata Kunci: Korelasi, Kosakata, Teks Cerita Fantsi